(5a - 4b) + (2c - 3b - 6c) + a =5a - 4b + 2c - 3b - 6c + a =(5a + a) + (-4b - 3b) + (2c - 6c) =[ 6a - 7b - 4c ].
-2a plus 3b
12a + 6b + 6c = 6(2a + b + c)
2a + 3b
6a+7b. This cannot be simplified anymore unless you know a or b.
The value of a in the equation 5a plus 2a = 6-6a is a=6/11.
4a + 3c - 2b - c + a - b = 5a - 3b + 2c
Gathering like terms together, this is equal to 5a + 3b + 7c.
The given expression can be simplified to: 3b-a
5a - 10 = 4a + 8 is a linear equation in one variable.
It is a linear equation in the variable a.
If: 2a+13 = 5a+1 Then: a = 4
5a-20+2a = 6a-11 5a+2a-6a = 20-11 1a = 9 a = 9